2008
DOI: 10.1182/blood-2007-04-083600
|View full text |Cite
|
Sign up to set email alerts
|

CREB is a critical regulator of normal hematopoiesis and leukemogenesis

Abstract: The cAMP-responsive element binding protein (CREB) is a 43-kDa nuclear transcription factor that regulates cell growth, memory, and glucose homeostasis. We showed previously that CREB is amplified in myeloid leukemia blasts and expressed at higher levels in leukemia stem cells from patients with myeloid leukemia. CREB transgenic mice develop myeloproliferative disease after 1 year, but not leukemia, suggesting that CREB contributes to but is not sufficient for leukemogenesis. Here, we show that CREB is most hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 44 publications
2
127
0
Order By: Relevance
“…Results demonstrated that CREB protein levels were high in HeLa and in all leukemia cell lines (Figure 1), but undetectable in sorted normal hematopoietic stem cells. On the contrary, ICER was not detected in any of the analyzed cell lines, but was expressed in normal hematopoietic cells (CD34À), supporting the association of CREB expression with leukemic tissue 19 and ICER with healthy tissue. The stable expression of ICER (HL60 þ ICER in Figure 1a), as well as the transient transfection of ICER (t ICER in Figure 1b) in HeLa and HL60 induced the reduction of the active phosphorylated form of CREB (P-CREB) compared with transfected controls (t EV).…”
Section: Icer Decreases Creb Expression In Hela and Hl60mentioning
confidence: 63%
“…Results demonstrated that CREB protein levels were high in HeLa and in all leukemia cell lines (Figure 1), but undetectable in sorted normal hematopoietic stem cells. On the contrary, ICER was not detected in any of the analyzed cell lines, but was expressed in normal hematopoietic cells (CD34À), supporting the association of CREB expression with leukemic tissue 19 and ICER with healthy tissue. The stable expression of ICER (HL60 þ ICER in Figure 1a), as well as the transient transfection of ICER (t ICER in Figure 1b) in HeLa and HL60 induced the reduction of the active phosphorylated form of CREB (P-CREB) compared with transfected controls (t EV).…”
Section: Icer Decreases Creb Expression In Hela and Hl60mentioning
confidence: 63%
“…Krüppel-like factor family members have been implicated in ES cell self-renewal, and Klf4 is one of the four transcription factors required to reverse the highly differentiated state of somatic cells back to pluripotency (17,38). Creb1/CREB1 has been demonstrated to be a critical regulator of both normal hematopoiesis and leukemogenesis (5,36). We propose that Cbp may further regulate the function of these networks at a subset of loci through acetylation of histone and nonhistone proteins , these critical cell fate decisions are altered, leading to an increase in quiescence and apoptosis, to preferential differentiation, and ultimately HSC exhaustion through decreased self-renewal (red arrows).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CREB controls critical cellular processes and is involved in the regulation of immortalization and malignant transformation (11). Recently, CREB was found to be overexpressed in many solid tumors of distinct histology when compared with normal adjacent tissues (12)(13)(14) and hematologic malignancies (3,15,16), which could be linked in some cases to tumor progression (14,17), decreased time to relapse, and decreased event-free survival of patients (18). On the basis of the important role of tumor progression, CREB represents a promising target for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain novel insights into the role of CREB activation in the malignant phenotype, in vitro models of ras-transformed cells represent suitable tools for such analyses. Because K-ras genes are often mutated in tumors of distinct histology, which is frequently associated with a poor prognosis and worse clinical outcome of patients (25,26) as well as resistance to targeted therapies (15,27), it was analyzed whether CREB contributes to the K-RAS V12 -transformed phenotype of murine fibroblasts and human K-RAS V12 -mutated colorectal carcinoma cell lines and lesions.…”
Section: Introductionmentioning
confidence: 99%